Agrimarketing System Development within the Frame of the EAEU Development and the Model of its Improvement - RAZAKOVA, Dina (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
This article is concerned with examination of the topical problems of agrimarketing system improvement and the formation of a new paradigm within the frame of the Eurasian Economic Union (EAEU)’s development. In the process of the study the theoretical basis of the agrimarketing system was analyzed in details and the marketing intricacies and peculiarities of agrifood businesses’ were defined. Special attention was paid to the distinguishing characteristics of agrimarketing in the EAEU, which were examined on the macro-, meso-, and micro levels. The model type of agricultural industrial policy (AIP) EAEU marketing system was suggested, its core and constituent composition was specified. Practical recommendations concerning the creation of the EAEU’s agrimarketing system were developed.